Econometric Fellows and Nobel Laureates in Economics - Ho Fai Chan; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
An academic award is method by which peers offer recognition of intellectual efforts. In this paper we take a purely descriptive look at the relationship between becoming a Fellow of the Econometric Society and receiving the Nobel Prize in economics. We discover some interesting aspects: of all 69 Nobel Prize Laureates between 1969 and 2011, only 9 of them were not also Fellows. Moreover, the proportion of future Nobel winners among the Fellows has been quite high throughout time and a large share of researchers who became Fellows between the 1930s and 1950s became Nobel Laureates at a later stage. On average, researchers become Fellows relatively early in their career (14.9 years after their PhD) and those who were subsequently made Nobel Laureates become Fellows earlier than other researchers. Interestingly, Harvard and MIT have been the dominant PhD granting institutions to generate Fellows and Nobel Laureates in the past.
Keywords: D71; A14; 330; Fellows of the Econometric Society; Nobel Laureate; ececonomics of science; awards